Cellular deoxyribonucleic-acid probes of two-photon-excited fluorescent quinolinium-substituted carbazole. Issue 4 (12th December 2018) - Feng, Yanru; Chi, Shuheng; Zhao, Yanli; Zhang, Yunjie; Wu, Yiqun
Abstract : Three new quinolinium-carbazole derivatives as deoxyribonucleic-acid probes irradiated with near-infrared-light have been designed and synthesized. Abstract : We report three new types of two-photon-absorption compounds, which contain a carbazole center core linked to two quinolinium units. Their action two-photon absorption cross-sections are 287.13, 267.75, and 236.25 GM. Under near-infrared excitation, their fluorescence emissions are observed at approximately 650 nm. The new compounds can stain deoxyribonucleic acid (DNA) with the same level of nuclear localization as that of Hoechst 33342. Under continuous irradiation with a near-infrared laser, the fluorescence decays of the three new compounds were less than those of 4, 6-diamidino-2-phenylindole; the average fluorescence decay rates were 0.014, 0.015, and 0.014% s −1 . They are expected to become new two-photon fluorescent probes of DNA.